Baseline demographics of a contemporary Belgian atrial fibrillation cohort included in a large randomised clinical trial on targeted education and integrated care (AF-EduCare/AF-EduApp study) - Delesie, Michiel; Knaepen, Lieselotte; Dendale, Paul; Vijgen, Johan; Ector, Joris; Desteghe, Lien; Heidbuchel, Hein (Frontiers in Cardiovascular Medicine, 2023)
Background As the prevalence of atrial fibrillation (AF) increases worldwide and AF management becomes ever more diversified and personalised, insights into (regional) AF patient demographics and contemporary AF management are needed. This paper reports the current AF management and baseline demographics of a Belgian AF population recruited for a large multicenter integrated AF study (AF-EduCare/AF-EduApp study). Methods We analyzed data from 1979 AF patients, assessed between 2018-2020 for the AF-EduCare/AF-EduApp study. The trial randomised consecutive patients with AF (irrespective of AF history duration) into three educational intervention groups (in person-, online-, and application-based), compared with standard care. Baseline demographics of both the included and excluded/refused patients are reported. Results The mean age of the trial population was 71.2 ±9.1 years, with a mean CHA2DS2-VASc score of 3.4 ±1.8. Of all screened patients, 42.4% were asymptomatic at presentation. Being overweight was the most common comorbidty, present in 68.9%, while 65.0% were diagnosed with hypertension. Anticoagulation therapy was prescribed in 90.9% of the total population and in 94.0% of the patients with an indication for thromboembolic prophylaxis. Of the 1979 assessed AF patients, 1232 (62.3%) were enrolled in the AF-EduCare/AF-EduApp study, with transportation problems (33.4%) as the main reason for refusal/non-inclusion. About half of the included patients were recruited at the cardiology ward (53.8%). AF was first diagnosed, paroxysmal, persistent and permanent in 13.9%, 47.4%, 22.8% and 11.3%, respectively. Patients who refused or were excluded were older (73.3 ±9.2 vs. 69.8 ±8.9 years, p<0.001) and had more comorbidities (CHA2DS2-VASc 3.8 ±1.8 vs. 3.1 ±1.7, p<0.001). The four AF-EduCare/AF-EduApp study groups were comparable across the vast majority of parameters. Conclusions The population showed high use of anticoagulation therapy, in line with current guidelines. In contrast to other AF trials about integrated care, the AF-EduCare/AF-EduApp study managed to incorporate all types of AF patients, both out-patient and hospitalised, with very comparable patient demographics across all subgroups. The trial will analyze whether different approaches to patient education and integrated AF care have an impact on clinical outcomes.